Inhibition of growth and metastasis of breast cancer in mice by milk fermented with Lactobacillus casei CRL 431 - de Moreno, Maria Alejandra (2015)
Breast cancer is the second cause of death in women, who are especially related to uncontrolled metastasis. It was previously demonstrated that the administration of milk fermented by Lactobacillus casei CRL 431 [fermented milk (FM)] delayed the tumor growth in a murine breast cancer model. In this work we evaluated if the administration of FM to mice, starting when the tumor was measurable, can affect not only the tumor growth, but also the extravasation of tumor cells and the lung metastasis. The evaluation of immune cells-infiltrating tumors and lungs was also performed. Tumor volume was calculated. Whole blood, lungs, and liver were processed to count the number of colonies formed by tumor cells. Blood serum was obtained for monocyte chemoattractant protein-1, interleukin (IL)-10, and IL-6 determination, lung tissues for histologic observations, and tumor tissues for angiogenesis determination. Mice that received FM were compared with animals given milk or to the controls without any especial supplementation. The results showed that FM administration to mice decreased or suppressed tumor growth, with less tumor vascularity, extravasation of tumor cells, and lung metastasis. These benefits were associated to modulation of the immune response by decreasing the infiltration of macrophages in both the tumor and the lungs. FM administration maintained an increased antitumor response associated to CD8 + lymphocytes, and also increased CD4 + lymphocytes that can be involved in the modulation of the immune response. The future evaluation of cytokine profiles will allow knowing more about subpopulation of macrophages and lymphocytes associated to the beneficial effect of this probiotic in the breast cancer model.